PERANAN METODE TUGAS TERSTRUKTUR DALAM MENINGKATKAN HASIL BELAJAR GEOGRAFI - Noviantoro, Kurnia Maulidi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2020)
The purpose of this research is to examine how the role of structured tasks to improve learning outcomes in geography. This research uses the literature study method. The approach is carried out with content analysis. The stages of this research are carried out by collected from various kinds of literature, analyzed, assessed, and finally drawn conclusions. The research findings conclude that structured assignments play a very positive role or impact in improving geography learning outcomes, and can stimulate students' motivation to learn. In addition, several other findings also revealed that in general structured tasks have a role in improving student learning outcomes and achievements, even in different levels and types of subjects.Keywords: role; structured task; learning outcomes